A comparison between approaches for the calculation of van der Waals interactions in flotation systems. (15th June 2021) - Weber, C.; Knüpfer, P.; Buchmann, M.; Rudolph, M.; Peuker, U.A.
Highlights: Data for Hamaker coefficient calculation of minerals. Van der Waals interactions between surfaces with adsorbed substances. Comparison between Lifshitz theory and approximate treatments. Abstract: Among the multitude of surface/interfacial forces, van der Waals forces have an impact on the performance of industrial processes in which dispersed substances such as drops, bubbles or particles are treated. The material dependent expression of the resulting forces is represented by the Hamaker function. This paper contains a selection of various methods for calculating the Hamaker function from the Lifshitz approach with a focus on heterocoagulation processes such as froth flotation. As an example, differences between the results of the full Lifshitz theory and approximate treatments are presented for selected Material - Water - Air systems. Such systems resemble the interaction between solids and air bubbles across water in flotation. In addition we present calculations of the Hamaker function in layered systems, which aim at modeling the adsorption of chemicals in flotation. Furthermore it is possible to treat so-called interfacial gas enrichment within this approach. Both, interfacial gas enrichment and adsorbed layers have a significant effect on the short-distance van der Waals interactions and increase the range of the interaction. The manuscript details the numerical solution of the Lifshitz equations and provides a list of the material properties required to calculate the Hamaker function for minerals.